PENGARUH PROMOSI, PERSEPSI HARGA DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MOBIL SUZUKI DI PT.ARISTA SUSKES ABADI TANJUNG PINANG - yudi yudi carsana (MANAJERIAL DAN BISNIS TANJUNGPINANG, 2020)
This study aims to determine the influence of promotion, price perceptions and consumer attitudes towards purchasing decisions of Suzuki cars at PT.Arista Suskes Abadi tanjung pinang The type of research used in this study is a type of quantitative research that explains a phenomenon about why and how things happen by using descriptive statistical methods, namely research that aims to test whether there is a relationship and the influence between independent and related variables. The research method used in this study was to use a questionnaire method and literature study conducted systematically. The sample in this study was 60 respondents. Processing data using the SPSS version 21.00 computer software program. This research has fulfilled the requirements for data validity and reliability. Analysis of the data used in this study is the Classical Assumption Test, Regression, Multiple Linear, Hypothesis Test, and Determination Coefficient Analysis. The results of this study indicate that based on partial testing it turns out that the results of the study prove that the promotion variable (X1), price perception (X2) and consumer attitudes (X3) have a significant influence on purchasing decisions, this can be seen promotion variable tcount 2.490> ttable value 2.00324 , price perception variable (5,697> ttable 2,00324) and then variable consumer attitudes (3,522> ttable 2,002). Based on simultaneous testing, the results of the study show that the value of Fcount> Ftable (53,512> 2.76). The conclusion of this study is that the variable promotions, price perceptions and consumer attitudes together influence the purchasing decisions of Suzuki cars at PT.Arista Suskes Abadi Tanjungpinang.